(untitled) (Móin-Móin - Revista de Estudios sobre Teatro de Formas Animadas, 2021)
The goal was to understand the current situation and give an overview of Baltic and Nordic countries’ puppet theater and puppet theater training traditions and whether and how the puppeteer’s profile has changed recently. To get an idea of the trends in this area, the common ground of the different countries, I interviewed theatre makers from Finland, Sweden, Norway, Latvia, Lithuania, and Estonia. The title of this research is "Tossed on the seas of visual theatre: challenges to puppetry’s survival as an independent discipline." To have a wider look at the puppetry, I also did two additional interviews. One of them with Marek Waszkiel - "Puppetry’s challenges in the new visual theatre paradigm" and another one with Russian director Yana Tumina - "The puppeteer in the 21st century".